2016
DOI: 10.1021/acs.orglett.6b03111
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt-Catalyzed Carbonylation of C(sp2)–H Bonds with Azodicarboxylate as the Carbonyl Source

Abstract: A novel and efficient approach for the C­(sp2)–H bond carbonylation of benzamides has been developed using stable and inexpensive Co­(OAc)2·4H2O as the catalyst and the commercially available and easily handling azodicarboxylates as the nontoxic carbonyl source. A broad range of substrates bearing diverse functional groups were tolerated. This is the first example where cobalt-catalyzed C­(sp2)–H bond carbonylation occurs with azodicarboxylate as the carbonyl source.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(29 citation statements)
references
References 46 publications
0
29
0
Order By: Relevance
“…Another carbonylation was reported in 2016 by Zhang, using diisopropyl azodicarboxylate (DIAD) as carbon monoxide surrogate. 441 Various arenecarboxamides were used, including compounds substituted with F, Cl, Br, CN, NO 2 , CF 3 or OMe and yields were typically around 70%. Several azodicarboxylates were also efficient for this reaction and three acrylamide derivatives were functionalised ( Scheme 71C ).…”
Section: Bidentate Dgsmentioning
confidence: 99%
“…Another carbonylation was reported in 2016 by Zhang, using diisopropyl azodicarboxylate (DIAD) as carbon monoxide surrogate. 441 Various arenecarboxamides were used, including compounds substituted with F, Cl, Br, CN, NO 2 , CF 3 or OMe and yields were typically around 70%. Several azodicarboxylates were also efficient for this reaction and three acrylamide derivatives were functionalised ( Scheme 71C ).…”
Section: Bidentate Dgsmentioning
confidence: 99%
“…Remarkably, when two different C( sp 2 )‐H bonds, the C−H bond at C5‐position of the quinoline and the ortho ‐C−H bond of the benzamide, were both present in the substrate (as in 1 o ), only amidation product 3 o , derived from functionalization of the C5‐position of the quinoline, was obtained (93% isolated yield) using our Ag‐catalyzed system. Interestingly, in 2016, Zhang and coworkers reported that the same substrate ( 1 o ) in the Co(OAc) 2 /Ag 2 CO 3 system gave carbonylation product 5 . In the same year, Baidya and coworkers independently reported that 1 o with DEAD in the Cu(OTf) 2 /Ag 2 CO 3 system gave amidation product 3 o (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…Zhang and co‐workers developed the carbonylation of 8‐amino quinoline benzamides 80 using readily available azodicarboxylates 129 as a non‐toxic carbonyl source (Scheme ) . This reaction is compatible with benzamides, vinyl amides and heteroaromatic amides to afford carbonylated products 130 .…”
Section: Insitu Generated High‐valent Coiii‐catalyzed Annulation Reacmentioning
confidence: 99%